"Mama Tikus" A Case Study of Illegal Trade And Smuggling at The Napan Border Nusa Tenggara Timur-Indonesia and Oekusi Enclave-Timor Leste - Nomleni, Anton Petrus Welland; Kameo, Daniel D.; Therik, Wilson (Pena Justisia: Media Komunikasi dan Kajian Hukum, 2024)
This article aims to provide an overview of the dynamics of women in Napan Village, North Central Timor Regency, in engaging in illegal trade and smuggling activities through informal routes with traders from the Oekusi Enclave, RDTL, hence earning the nickname "Mama Tikus" (Rat Mama). The trade conducted through these informal routes involves various commodities, including non-subsidized manufactured goods and local agricultural and plantation products. In response to pressure from "Mama Tikus" and other members of the community, the local government has implemented a responsibility policy with mechanisms agreed upon by these traders, allowing them to conduct their transactions smoothly. Furthermore, the perspective of Caroline Lesser & Evdokia Moise-Leema  categorizes the illegal trade and smuggling of commodities in the Napan area into three categories: Category A: Informal/unregistered traders or firms operating entirely outside the formal economy, including individuals like "Mama Tikus," who engage in economic activities without formal registration as traders but conduct trade and transactions with parties from Oekusi-RDTL. Commodities traded include a thread for traditional weaving, tamarind, porang, and cowhide, as well as local agricultural and livestock products. Category B: Formal/registered firms fully evading trade-related regulations and duties, such as avoiding official border crossing posts. This category pertains to non-subsidized manufactured goods traded by merchants without going through customs or via informal routes. Examples include soap, toothpaste, instant noodles, cooking oil, electronics, flour, soft drinks, alcoholic beverages, cigarettes, and other commodities.